THE INFLUENCE OF VIDEO-ASSISTED PROBLEM BASED LEARNING MODELS ON LEARNING OUTCOMES ON THE CONCEPT OF ELASTICITY AND HOOKE'S LAW IN HIGH SCHOOL - Sri Astri Suo; Abdul Haris Odja; Nova Elysia Ntobuo (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
This research aims to provide an overview of how the influence of learning using problem based learning models through blended learning assisted video on the concept of elasticity and hooke law to the learning outcomes of students in high school 2021/2022, in class XI IPA odd semester 2021/2022 with one class as an experimental class. The method used in this study was pre-experimental with the design of One Groups Pretest-Posttest. Data collection of learning results is done based on the assessment of test results. Analysis of research data using, hypothesis tests and n-gain tests. Based on hypothesis testing, the calculated price of class XI IPA 2, 9.68 where for the table price for the three classes is Class XI IPA 2,779, H0 is accepted and H1 is rejected. This shows that learning uses a problem based model assisted by video. Judging from the average pretest and posttest grades of students from experimental classes, it can be concluded that there is an influence on problem based learning models through blended learning assisted video on students' learning outcomes on the concept of elasticity and hooke law with n-gain high criteria.